Analyzing the Effects of Work Motivation, Work Discipline, and Work Environment on Civil Servant Performance with Organizational Commitment as an Intervening Variable - Jovanka Pittaloka; Simon Sia Niha; Henny A. Manafe; M. E. Perseveranda; Stanis Man (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to describe the performance, organizational commitment, work motivation, work discipline, and work environment of civil servants at S.K. Lerik Regional General Hospital in Kupang City, as well as to analyze how these factors influence organizational commitment and employee performance. Using a sample of 72 civil servants, data were collected through questionnaires and analyzed using descriptive statistics and SmartPLS. The descriptive results indicate that employee performance, organizational commitment, motivation, and work discipline are generally good, while the work environment is considered fairly good. The inferential findings show that work motivation, work discipline, and work environment each have a positive and significant effect on organizational commitment and employee performance. These results highlight the importance of strengthening motivational factors, improving discipline, and enhancing the work environment to support higher commitment and performance among civil servants.